El català del País Valencià dels segles XVII i XVIII - Martí Mestre, Joaquim (Caplletra. Revista Internacional de Filologia, 2017)
This essay vindicates the interest of the study of 17th and 18th century Valencian, in opposition to traditional stereotypes that derogatively classify it as presumably a period of literary and socio-linguistic decline. Summing up previous works and with a large new body of evidence, the author describes the most significant morpho-syntactical characteristics of the Valencian varieties of this period, in contrast to precepts of the contemporary norm and to the present state of Valencian.